2022
DOI: 10.3389/fpsyt.2022.839630
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Contribution of Past Bullying Experiences to the Presence of Psychosis-Like Experiences in University Students

Abstract: ObjectivesBoth bullying and psychosis-like experiences (PLEs) have gained much attention in recent years, but their interactions are not fully unraveled. The aim of the current study was to validate the Chinese version of Bullying Scale for Adults (C-BSA), and to investigate whether past bullying experiences independently predict the presence of PLEs in university students.MethodsThe validity and reliability of the C-BSA were determined in two independent samples. A battery of psychological inventories was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
2
0
1
Order By: Relevance
“…Last, Part C includes two items that inquire about the experience of acting as a bullying perpetrator. Our previous study yielded favorable outcomes in terms of reliability and validity in the Chinese version of the BSA ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…Last, Part C includes two items that inquire about the experience of acting as a bullying perpetrator. Our previous study yielded favorable outcomes in terms of reliability and validity in the Chinese version of the BSA ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…Giovaziolas & Malikiosi-Loizos, 2016;Kokkinos et al, 2016;Spanou et al, 2020) have shown a strong interest in the topic. Other countries where bullying in higher education has been the subject of research include China (Su et al, 2022;Zhao et al, 2022), India (Kaur & Kaur, 2023;Sinha & Bondestam, 2022), Pakistan (Ahmed et al, 2022), South Africa (Badenhorst & Botha, 2022), Spain (Yubero et al, 2023), Turkey (Akbulut & Eristi, 2011) and the United Arab Emirates (Al-Damarki et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Perundungan dikaitkan dengan 2.0 atau 3.7 kali risiko untuk mengalami PLE (Zhao et al, 2022). Dukungan emosional, instrumental, dan informasi dari guru, rasa memiliki siswa, lingkungan sekolah yang kooperatif, dan iklim disiplin kelas memainkan peran penyangga dalam korban perundungan, sementara persaingan di lingkungan sekolah secara negatif meningkatkan paparan perundungan secara keseluruhan (Zhu & Teng, 2022).…”
Section: Pendahuluanunclassified